Predicting intention to use alternative dispute resolution (ADR): an empirical test of theory of planned behaviour (TPB) model - Lee, Chia Kuang; Yiu, Tak Wing; Cheung, Sai On (Taylor & Francis, 2018)
Alternative dispute resolution (ADR) has gained prevalent interests among practitioners and researchers. To better explain the factors underpinning the use of ADR, Theory of planned behaviour (TPB) model was applied to predict behavioural intention to use ADR. In general, the TPB model posits that attitude, subjective norm and perceived behavioural control explain actual behaviour. Therefore, this study investigates the role of attitude, subjective norm and perceived behavioural control towards the prediction of intention in ADR use. Data were collected from 128 ADR decision makers from Malaysian contractor firms. Both measurement and structural assessment of the model were performed by using Partial Least Squares (PLS) modelling. The results showed that TPB model provides excellent predictive accuracy and relevance for intention. The model was again examined in two distinctive scenarios. Attitude was found to be the sole predictor of intention in the occurrence of dispute; and before negotiation fails. The findings indicate a plausible future empirical investigation in the attitudinal dimension.